FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA KARYAWAN BAGIAN PRODUKSI BENANG DI PT. ISKANDAR INDAH PRINTING TEXTILE SURAKARTA - Fayza Nawang Darma Putra; Rezania Asyfiradayati (Universitas Pahlawan Tuanku Tambusai, 2023)
Performance is a measuring tool for achieving organizational goals. There are several elements that affect employee performance, including lack of commitment, lack of desire, lack of discipline, and the heavy workload given by the employer. factors affecting employee performance. The factors that influence performance are individual factors, psychological factors and organizational environmental factors. Work facilities and company rules including overtime here are very important so that employees feel comfortable at work including avoiding work fatigue. This study aims to identify factors related to employee performance at PT. Iskandar Indah Printing Textile Surakarta. In this study using purposive sampling method. There is a significant relationship between age and the performance of employees in the yarn production department at PT.Iskandar Indah Printing Textile Surakarta. There is a significant relationship between gender and the performance of employees in the yarn production department at PT. Iskandar Indah Printing Textile Surakarta. There is no relationship between length of service and employee performance in the yarn production department at PT. Iskandar Indah Printing Textile Surakarta. There is a significant relationship between work fatigue and the performance of employees in the yarn production section at PT.Iskandar Indah Printing Textile Surakarta.